2020
DOI: 10.37932/j.e.v9i1.51
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Dan Dampaknya Terhadap Loyalitas Karyawan

Abstract: The research aims to analyze empirical evidence of the influence of leadership style on employee performance and its impact on employee loyalty on PT. Fastrata Buana Branch Pulogadung. Samples obtained by 187 respondents, sample retrieval techniques using purposive sampling, namely sample retrieval techniques that provide equal opportunities for each element (member) of the population to be selected to be a sample member. Data collection techniques using questionnaires, data analysis techniques used are validi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 0 publications
1
2
0
6
Order By: Relevance
“…The results of this study are supported by the results of research presented by Ohemeng, Amoako-Asiedu, and Obuobisa (2018), which reveals that simultaneously leadership style and work discipline affect employee performance. Meanwhile, the results of this study are partially supported by Makambe & Moeng (2019) and Jayanti & Wati (2019), Irwan, Adam, Sofyan, Mustanir, & Fatimah (2019). The research results by Ohemeng et (2018) concluded that leadership style has a significant effect on employee performance.…”
Section: Table 1 Description Of Leadership Stylesupporting
confidence: 65%
“…The results of this study are supported by the results of research presented by Ohemeng, Amoako-Asiedu, and Obuobisa (2018), which reveals that simultaneously leadership style and work discipline affect employee performance. Meanwhile, the results of this study are partially supported by Makambe & Moeng (2019) and Jayanti & Wati (2019), Irwan, Adam, Sofyan, Mustanir, & Fatimah (2019). The research results by Ohemeng et (2018) concluded that leadership style has a significant effect on employee performance.…”
Section: Table 1 Description Of Leadership Stylesupporting
confidence: 65%
“…Uji hipotesis yang digunakan dalam penelitian ini adalah uji t dan uji f. Indikator pengembangan instrumen dapat dilihat pada tabel 1. (Gunawan, 2017) Loyalitas Karyawan 1) Taat pada peraturan 2) Tanggung jawab 3) Pengabdian 4) Rasa memiliki 5) Hubungan antar karyawan 6) Kejujuraan (Jayanti & Wati, 2020)…”
Section: Metode Penelitianunclassified
“…According to Jayanti & Wati (2019), the higher the level of employee loyalty will foster a sense of employee loyalty to the company and the trust given, so that they can complete the task optimally in order to achieve the targets set by the company.…”
Section: Loyalty Of Employees Of Ppl Companies In Sidoarjo a Responsi...mentioning
confidence: 99%